Minor Capacity Analysis of N Major Traffic Streams at Intersection - Yang Xuehui; Luo Gaogui (Indonesian Journal of Electrical Engineering and Computer Science, 2012)
Based on the gap acceptance theory, this paper analyzed running state of the intersection streams about the main traffic priority controls. Theories were used in this paper, such as gap theory, the probability theory and the calculation methods of minor capacity under two vehicle streams. The calculating formula of minor capacity for n main vehicle streams was derived under the conditions of M3 distribution by the main stream headway at the uncontrolled intersection. DOI: http://dx.doi.org/10.11591/telkomnika.v10i8.1636